International investment law and sustainable development - Schacherer, Stefanie; Hoffmann, Rhea (Research Handbook on Foreign Direct Investment, 2019)
The chapter looks at the relationship between sustainable development and international investment and seeks to highlight the aspects of international investment law that are relevant within the context of achieving sustainable development such as key substantive investment norms. The chapter examines investment promotion as well as investment facilitation, which may be conditioned on sustainable development objectives or may be more accurate to serve the goal of sustainable development. Another section of the chapter is dedicated to investor-State dispute settlement and sustainable development looking at – on the one hand – investment treaty cases with sustainable development implications as well as the design of investor-State dispute settlement on the other hand. Furthermore, the role of impact assessments and specific chapters on sustainable development in free trade agreements are highlighted. Finally, the chapter concludes with pointing out some future research questions with respect to sustainable development and international investment law.
CRIS-Team Scopus Importer:2024-12-16